Influence of climate change on the Ria de Aveiro littoral: adaptation strategies for flooding events and shoreline retreat - Dias, João M.
Floods and shoreline retreat in coastal areas threaten many millions of people across Europe. Moreover, it is agreed that climate change can amplify the magnitude and frequency of flooding events and accelerate the shoreline retreat. The main goal of this work is to assess flood and shoreline retreat risk, and define adaptation strategies under present conditions and future climate change scenarios on the Ria de Aveiro and its littoral. The hydrodynamic model ELCIRC was implemented for the Ria de Aveiro lagoon and GENESIS (U.S. Army Corps of Engineers) and LTC (Long-Term Configuration) shoreline evolution models for the littoral stretch between Esmoriz and Mira. Numerical results in present and future scenarios were used to map the flooded lagoon extension and the shoreline evolution of this coastal stretch. Analysis showed an increase of the lagoon’s flooded area, relative to the present, with regions more exposed to sea level rise being lowland areas located at the margins of the lagoon’s deeper channels. Examination of the littoral stretch showed a slight increasing trend of shoreline retreat under predicted future climate change scenarios, thereby increasing the probability of sand spit rupture. Data from numerical predictions were integrated into Geographical Information Systems covering the coastal and lagoon study areas, and produced hazard and risk maps including the identification of regional use and activities. Structural and non-structural measures were subsequently developed in order to mitigate flood and shoreline retreat effects.